2016
DOI: 10.1097/pai.0000000000000326
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Immunophenotypic Characterization of Adult and Fetal Testes, the Excretory Duct System, and Testicular and Epididymal Appendages

Abstract: The immunophenotype of a normal testis and the excretory duct system has not been studied comprehensively in fetal and adult patients without testicular disease or hormonal manipulation so far. In addition, testicular (TA) and epididymal (EA) appendages are frequent paratesticular structures without previously reported comprehensive immunophenotypic studies. Immunohistochemistry for multiple markers, including the androgen receptor (AR), the estrogen receptor (ER), the progesterone receptor (PR), the prostate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
3
13
0
Order By: Relevance
“…They found that the normal epididymis expressed CK7 (strong, diffuse), PAX8, and AR (variably). 28 The epididymis-like tubules in all 3 of our cases showed a similar pattern. Chen and Chang 24 demonstrated PAX2 expression (which is similar to PAX8) in the epithelium of the primitive tubules in renal dysplasia.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…They found that the normal epididymis expressed CK7 (strong, diffuse), PAX8, and AR (variably). 28 The epididymis-like tubules in all 3 of our cases showed a similar pattern. Chen and Chang 24 demonstrated PAX2 expression (which is similar to PAX8) in the epithelium of the primitive tubules in renal dysplasia.…”
Section: Discussionsupporting
confidence: 67%
“…The epididymis-like tubules in our study showed not only a morphological similarity to the epididymis but also displayed an identical immunohistochemical profile. Magers et al 28 characterized the immunophenotype of the normal testes and the excretory system and concluded that each anatomical region had a unique and reproducible immunohistochemical profile. They found that the normal epididymis expressed CK7 (strong, diffuse), PAX8, and AR (variably).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this strong reactivity raises the differential diagnostic consideration with ccRCC even more so. Likewise, it is well known that pax-8 expression is found in many normal and neoplastic tissues, including epididymis, rete testis, fallopian tumor and ovary, pancreatic islets and lymph nodes, while commonly found in bladder adenocarcinoma, seminoma, endometrial adenocarcinoma, ovarian serous carcinoma, renal cell carcinoma, oncocytoma, neuroendocrine tumors, parathyroid carcinoma and papillary, follicular and medullary thyroid carcinoma [43][44][45][46][47][48][49]. During embryogenesis, pax-2 and pax-8 transcription factors play a redundant role by together regulating inner ear development, associated with otic placode induction, where they are required to maintain otic differentiation [50,51].…”
Section: Discussionmentioning
confidence: 99%